Energy analysis and modelling - Yeo, Wei Ling. (2009)
The overall objective of the study is to provide reliable information on key factors affecting the economics of electricity generation using a range of technologies for Singapore. To address these issues, an energy model of Singapore from 2000 to 2030 is developed using the MARKAL framework